The concept of the 'carcinoid': The phylogenic and ontogenic evolution of the unresolved karzinoide conundrum. (June 2021) - Modlin, Irvin M.; Kidd, Mark
Abstract: In respect of carcinoid disease, one might well ask, why have we failed so miserably? In 1907, Oberndorfer described "karzinoide" and yet more than a century later, most diagnoses still reflect incurable metastatic disease. Attempts to address the biology and mechanistic basis of neuroendocrine tumors (NETs) have lacked logic, balanced oversight, or linearity. Governance appears directed to the support of countless clinical trials, often so underpowered and scientifically improbable as to seem based more on marketing premise than medicine. Much science is devoted to the development of potentially commercial applications rather than the elucidation of the mechanisms of neoplastic biology. A variety of organizations with quasi-scientific or commercial interests purport to drive research and diverse studies with no apparent focus or prioritization. Goals more often appear to seek popular acclaim and to accommodate the vogue of public debate by enthusiastic and often uninformed advocates of progress ( sic ) than to logically address the acquisition of information necessary to facilitate diagnosis and effect cure. Innumerable iterations of tumor nomenclature have been pondered over and discarded as if semantics might effect a cure or theological debate might inform science. Publications are often permutations and commutations of previous work and do little more than plump up personal bibliographies. Innumerable "disease observations" continue to be published, much in the mode of the reports of the early discovers of the globe-like sightings of exotic apparitions or more often, merely "me too" reflections. Treatments have been almost completely co-opted from other cancers and, in the most part, found to be wanting or misleading in their efficacy. Guidelines, eminence based and society based, continue to be presented with metronomic regularity and adopted by "followers"; more remindive of religious exhortations to the faithful endlessly in pursuit of Hippocratic grail. Some progress has been made—somatostatin receptor identification (40 years ago), sundry quasi-effective drugs, theranostics, and receptor targeting—but unfortunately, the molecular mechanistic basis of NETs remains so inadequately defined as to obviate any intervention based on a plausible hypothesis. There needs to be input from persons wise in science, clinical medicine, and strategy development to define rational steps forward to a series of defined goals rather than an interface of the marketplace and client dialog. Short-, intermediate-, and long-term goals need to be defined and developed rather than random excursions into the hinterland of an uncharted disease. Overall, what is obligatory for advance is the development and integration of novel technologies—molecular, mathematical, multianalytic, and genomic based—to provide the biological basis for elucidation of the disease and the development of personalized clinical management. The neuroendocrine community must move beyond the endless and relatively ineffective iterations of known knowledge and define new ways forward. Some work of noble note may yet be done; T'is not too late to seek a newer world, but strong in will to strive, to seek, to find (Adapted from Alfred Lord Tennyson, 1842).